ORIGINAL RESEARCH - Ciprian Camil Mireştean; Anda Crişan; Liliana Eleonora Semenescu; Adina Mitrea; Florinel Bădulescu (Oncolog-Hematolog.ro)
The evolution of the neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio during polychemotherapy in head and neck cancers Imaging of pericardial compressive syndromes – cardiac tamponade in oncologic patients